ESTIMATION OF DIFFUSION CONSTANTS BY OBSERVATIONS OF ISOKINETIC EFFECTS: A TEST FOR RADIOGENIC ARGON AND STRONTIUM - Voltaggio M. (My University, 1985)
A method of estimating unknown diffusion constants, by testing isokinetic effects, is briefly outlined. The calculated Ar rad and Sr rad diffusion constants agree well with experimental data. The employment of the method is suggested for the setting up of diffusion experiments.